Cytoskeleton organisation during the infection of three brown algal species, Ectocarpus siliculosus, Ectocarpus crouaniorum and Pylaiella littoralis, by the intracellular marine oomycete Eurychasma dicksonii. (22nd May 2013) - Tsirigoti, A.; Küpper, F. C.; Gachon, C. M. M.; Katsaros, C.; Wick, S.
Abstract Oomycete diseases in seaweeds are probably widespread and of significant ecological and economic impact, but overall still poorly understood. This study investigates the organisation of the cytoskeleton during infection of three brown algal species, Pylaiella littoralis, Ectocarpus siliculosus, and Ectocarpus crouaniorum, by the basal marine oomycete Eurychasma dicksonii. Immunofluorescence staining of tubulin revealed how the development of this intracellular biotrophic pathogen impacts on microtubule (MT) organisation of its algal host. The host MT cytoskeleton remains normal and organised by the centrosome until very late stages of the infection. Additionally, the organisation of the parasite's cytoskeleton was examined. During mitosis of the E. dicksonii nucleus the MT focal point (microtubule organisation centre, MTOC, putative centrosome) duplicates and each daughter MTOC migrates to opposite poles of the nucleus. This similarity in MT organisation between the host and pathogen reflects the relatively close phylogenetic relationship between oomycetes and brown algae. Moreover, actin labelling with rhodamine‐phalloidin in E. dicksonii revealed typical images of actin dots connected by fine actin filament bundles in the cortical cytoplasm. The functional and phylogenetic implications of our observations are discussed.